Tindak Pidana Korupsi Sebagai Pelanggaran Hak Asasi Manusia - M. Ilham Wira Pratama (Universitas Islam Indonesia, 2019)
Corruption has been categorized as extraordinary crime, because it does not only harm the country’s finances, but it is also a violation of the social and economic rights of the community. Accordingly, it can be seen that there is a link between corruption and human rights violation, namely the fundamental social and economic rights of the community. In addition, there is a Court Decision on corruption that ascertains human rights violation as an aspect for the judges' consideration, which is the Supreme Court Decision Number 1616 K/Pid.Sus/2013. Thus, it is necessary to acknowledge: is corruption a violation of human rights? What are the criteria for corruption to be deemed as a violation of human rights? Why the criteria for corruption to be deemed as a violation of human rights need to be taken into consideration by the judge in passing the decision? The type of this study is normative legal research by using two methods which are statute and philosophical approaches, to be analyzed qualitatively and presented descriptively. The results show that there is a link between corruption and human rights violations, corruption is categorized as a violation of human rights if the criminal act of corruption intersects with the violated human rights, therefore human rights violation caused by corruption should be made as a consideration by judge in his decision because the judge’s decision must be comprehensive in order to realize an ideal decision that reflects the value of justice, legal certainty, and legal benefits, and on the other hand, human rights is a fundamental element, therefore it should not be ignored in the judge’s consideration in making the verdict.